Factors Associated with Quality of Intrapartum Care in Kenya: a Complex Samples Analysis of the 2022 Kenya Demographic and Health Survey - Nuwabaine, Lilian; Amwiine, Earnest; Sserwanja, Quraish; Kawuki,Joseph; Amperiize, Mathius; Namulema, Angella; Asiimwe, John Baptist (ResearchSquare, 2024)
Quality of intrapartum care remains a key intervention for increasing women’s utilization of skilled birth attendants in health facilities and improving maternal and newborn health. This study aimed to investigate the factors associated with the quality of intrapartum care using the 2022 Kenya Demographic and Health Survey (KDHS). Secondary data from the 2022 KDHS of 11,863 participants, who were selected by multistage stratied sampling, was used. Quality of intrapartum care was considered if a mother had a facility-based delivery, received skilled assistance during birth, and the baby immediately placed on the mother’s breast by skilled birth attendant within 1 hour after birth. We conducted multivariable logistic regression to determine the factors associated with quality of intrapartum care using SPSS (version 20).